Validity and reliability of the WHOQOL-BREF in a pregnant population - Rondung, Elisabet (2023)
Background: Physical end emotional changes during pregnancy may not only affect pregnant womens’ quality of life, but also how instruments assessing quality of life perform in such populations. To date, there is insufficient evidence on psychometric properties for both generic and condition-specific instruments measuring quality of life during pregnancy. The aim of this study was thus to examine the structural validity, internal consistency, and construct validity of the WHOQOL-BREF in a sample of pregnant women. Methods: A convenience sample of 1015 pregnant women in Sweden completed the WHOQOL-BREF online. We examined the psychometric properties of the instrument using principal component analysis (PCA), confirmatory factor analysis (CFA), Cronbach’s alpha, item-domain correlations, correlations with overall QOL and general health, and multiple linear regression with items on overall QOL and general health as outcomes. Results: Principal Component Analysis in a random subsample (n = 502) supported a four-factor model, encompassing the domains physical, psychological, social and environmental quality of life, but with four of the items originally in the environmental domain relocated to the other domains. The proposed domain structure showed good fit in confirmatory factor analysis in the other random subsample (n = 513). The physical and psychological domains showed good internal consistency (Cronbach’s alpha = 0.885 and 0.826 respectively), while the social and environmental domains were weaker in this regard. All domains showed significant positive correlations with items on overall QOL and general health. The physical and psychological domains were the most evident predictors in the regression models. Conclusions: We find the Swedish version of the WHOQOL-BREF to have good psychometric properties to be used in samples of pregnant women, and propose an alternative domain structure that might be even more useful for assessing quality of life during pregnancy. The physical and psychological domains showed good internal consistency and construct validity.